2015
DOI: 10.1128/aem.03138-14
|View full text |Cite
|
Sign up to set email alerts
|

Prepartum and Postpartum Rumen Fluid Microbiomes: Characterization and Correlation with Production Traits in Dairy Cows

Abstract: cMicrobes present in the rumen of dairy cows are essential for degradation of cellulosic and nonstructural carbohydrates of plant origin. The prepartum and postpartum diets of high-producing dairy cows are substantially different, but in what ways the rumen microbiome changes in response and how those changes may influence production traits are not well elucidated. Here, we sequenced the 16S and 18S rRNA genes using the MiSeq platform to characterize the prepartum and postpartum rumen fluid microbiomes in 115 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

37
149
5
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(194 citation statements)
references
References 47 publications
(50 reference statements)
37
149
5
3
Order By: Relevance
“…Moreover, research focused on the development of the ruminal community over time has relied primarily on calves (3-6, 23, 37) or a limited number of time points with adult animals (20, 23) and thus could not include data on the efficiency of downstream milk production. To date, studies on the ruminal microbiota of dairy cows in relation to their milk production metrics have been limited by restricted sampling periods (12,20), making it difficult to address issues of long-term community stability with host metrics. In this study, we tracked the ruminal bacterial community, feed consumption, and milk production over the course of 2 years, including three stages within each lactation cycle.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, research focused on the development of the ruminal community over time has relied primarily on calves (3-6, 23, 37) or a limited number of time points with adult animals (20, 23) and thus could not include data on the efficiency of downstream milk production. To date, studies on the ruminal microbiota of dairy cows in relation to their milk production metrics have been limited by restricted sampling periods (12,20), making it difficult to address issues of long-term community stability with host metrics. In this study, we tracked the ruminal bacterial community, feed consumption, and milk production over the course of 2 years, including three stages within each lactation cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Feed efficiency in dairy cattle is known to be affected by a variety of factors, including host genetics, environmental conditions such as ambient temperature, the various metabolic contributions and demands of pregnancy, tissue mobilization, and immune response. Moreover, recent studies have reported that the composition of the ruminal microbial community is associated with differences in several drivers of feed efficiency (2, 12-15), milk yield and composition (12,(16)(17)(18)(19), and alterations in pregnancy stage (20).Recent work using high-throughput sequencing technology has revealed correlations between the abundance of particular ruminal bacterial genera with milk composition and RFI, although these determinations did not consider changes over entire lactation cycles (12,20). Given that milk production is altered by major physiological shifts associated with stage of lactation and pregnancy (6, 21), it is necessary to consider that time may be a significant variable in the composition of the ruminal microbial community.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Addressing the gaps in current understanding of the rumen microbial ecosystem 41 is therefore key to the development of new strategies to control the microbial populations. The rumen contains a very dense microbial ecosystem, endproducts of microbial digestion, salts and plant material including partially digested fibre, carbohydrate, and phenolic compounds and as such, samples of rumen material often present unique technical challenges.…”
Section: Future Directionsmentioning
confidence: 99%